Investigation on the MHz-THz Radiation Field Regime Absorption in Cancer-Health Cell Tissue - Muhamad Hamdi; Usman Malik (Universitas Riau, 2014)
This paper focuses on the thermoregulation rise due to exposure of the MHz-THz radiation field regime in cancer-health cell tissue. In fact it may occur some processes such as absorption, transmission, reflection and scattering when this radiation interacts with tissue. It depends on the exposure power source. During in cell tissue there is basically the existence of this radiation field contribution to the cell tissue bioelectric and bio magnetic field result in heat production rate. It has a source from excitations of cell macromolecule photonic-phonon vibrations. The self cell tissue has the periodic bio potential with a small cellular volume results in the bioelectric field. This main reason we investigate and solve the simultaneous equations using Maxwell, heat conduction and sinusoidally modulated intensity equation with spectral method. We assume a small tissue piece to form the spherical or cylindrical cell membrane layer. Absorption involves the extraction of vibration energy from MHz-THz radiation regime field by a cell macromolecular species; the vibration must cause a change in the cell electric dipole moment. Energy absorption is the primary mechanism that allows radiation field of MHz-THz source to produce physical effects on tissue for treatment purposes. While transitions between two energy levels of a molecule that are well defined at specific THz wavelengths could serve as a spectral fingerprint of the cancer molecule for diagnostic purposes.